OTONOMI PEREMPUAN DALAM PENGAMBILAN KEPUTUSAN BER-KB (Analisis Data SDKI 2007) - , RETNO DEWI PUSPITA SARI, S.SOS, Dr. Anna Marie Wattie, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The transition of population policies from target oriented to the fulfillment of reproductive rights in accordance with the mandate of ICPD 1994 is not supported by the position of women within household. This happens because there are different views about the position of women and men in society, therefore, the rights and the responsibilities of they were considered different. The subordinate women within household can causing the lack of women who can expressing opinions in front of the couple (husband). Womenâs autonomy in family planning decision-making are very essential for women because it is concerning of their reproduction and their own body. This study was conducted to analyze the influence of personal resources variables (education, work status, economic contribution and employment sector) towards womenâs autonomy in family planning decision-making. This study using the theory of Feminist Liberal, with the assumption that the links between women's involvement in the public sector and autonomy are part of the liberal feminist discourse. The data source was from IDHS 2007. by using samples of ever married women who are using family planning methods at the time of survey (n=18.037). The statistical test using crosstab, chi square and logistic regression binary. The tendency and effect relationship seen through the significance level at 5% (p<0,05). The result of multivariable analysis showed that the employment sector has positive significant effect towards women's autonomy in family planning decision-making, while other variables such as work status and economic contribution has no significant effect. Education has negatif significant effect. Some things that can explain these results: First, the strength of the value contained in the society about the different position of women and men, so that womenâs involvement in the public sector is never be separated from the role of womenâs in the domestic sector. Second, the persistence of stigma from the society that family planning is related to women's affairs, so that women are always faced with the difficult choices to determine a safe contraceptive for herself. The results of this research adds a note of criticism for liberal feminists that women's involvement in the public sector does not automatically improving women's status and womenâs autonomy within the household. The discourse of womenâs involvement in development should be supported by the existence of gender transformation.